Implementation of Regression Analysis to The Influence of Democratic Leadership, Communication, Work Culture, and Ability on Employee Performance in Regional Development Planning Agency Labuhanbatu District - Muhammad Rizky Nugraha; Siti Lam'ah Nasution; Nova Jayanti Harahap (PT Mattawang Mediatama Solution, 2023)
This study aims to analyze The Influence of Democratic Leadership, Communication, Work Culture and Capability on Employee Performance at the Regional Development Planning Agency of Labuhanbatu Regency. The research method used in this research is quantitative. In this study, the population consisted of 60 employees of the Labuhanbatu Regency Regional Development Planning Agency. The research sample usesSampling technique is saturated by attracting the entire existing population to be used as a research samplea total of 60 people. Data collection techniques used were observation, documentation studies and questionnaires. The method of analysis of this research is multiple linear regression with the SPSS program. The research results prove that Democratic Leadership positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency. Communication positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency. Work Culture positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency. Ability positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency. Democratic Leadership, Communication, Work Culture And Capability simultaneously positive and significant effect on Employee Performance at the Regional Development Planning Board of Labuhanbatu Regency. The coefficient of determination is 0.732, meaning that employee performance can be explained by variables Democratic Leadership (X1), Communication (X2), Work Culture (X3) and Ability (X4) of 79.7%, while the remaining 20.3% can be explained by other variables not examined in this study.